Effects of supervised exercise intervention on tobacco withdrawal Ssymptoms during temporary smoking abstinence / Nur-Hasanah Ruslan - Ruslan, Nur-Hasanah (2021)
Tobacco withdrawal symptoms (TWS) occur following smoking abstinence and are a barrier to quit smoking. Recently, exercise found to be an adjunct treatment for smoking cessation. This study’s objectives were to examine the effects of an exercise intervention on TWS among sedentary to minimally active male smokers. This study aimed to investigate whether exercise affects the physiological, psychological and hormones, namely serum cortisol, serum beta-endorphin, and plasma adrenaline, are involved in regulating TWS and exploring the experience of an exercise intervention on abstinence related feeling. This study consists of three phases, starting with a validation study of the study instrument, followed by an intervention and qualitative study. The validation study involved the validation process for study instruments for the intervention study. The intervention study carried out with a convenience sampling method. Thirty healthy smokers were recruited from various institutions and were given an exercise intervention programme for two months. Then, fourteen smokers that underwent the intervention were interviewed for the qualitative study. For the validation study, exploratory and confirmatory factor analyses were performed. The intervention study was analysed using Repeated Measure ANOVA and correlation. The result of the qualitative study was analysed using thematic analysis. This study found a significant reduction in (craving, urge components), improved mood, increased adrenaline, and a favourable trend of the study variables following the exercise intervention. The qualitative study found that most participants perceived benefits of an exercise intervention on TWS and smoking habit. In conclusion, exercise intervention found to improve certain study variables. Thus, exercise can help reduce TWS for smoking cessation and recommend designing the smoking cessation programme.